Feeling a historic city: Porto landscape through the eyes of residents and visitors - Freitas, I.; Sousa, C.; Makhabbat Ramazanova; Albuquerque, H. (International Journal of Tourism Cities, 2022)
Purpose - This paper aims to monitor the urban landscape through the perceptions of residents and visitors, identifying features that cause visual impacts and providing insights for landscape management decision-makers. Captured impressions about the city whilst moving around are important to assess the satisfaction of city residents and city visitors through key elements, such as directional signage, outdoor advertising, restaurants’ outdoor terrace furniture, urban furniture, green spaces, traffic, cleaning, pedestrian areas, visitor flow and conservation of monuments, museums and buildings. Design/methodology/approach - A survey was applied in the historical Porto city centre (Portugal) to understand residents’ and visitors’ perceptions of the city landscape and assess the differences between these two groups. Cronbach’s alpha was used to assess the reliability of the constructs (dimensions) of urban landscape. Non-parametric Mann-Whitney test was used to find significant differences in the perceptions of residents and visitors. Findings - The results suggest significant differences in the perceptions. Residents value more two constructs of the landscape (heritage conservation and transport mobility) whilst visitors value more other two (pedestrian mobility and aesthetic quality). It is showed that residents have a strong sense of place and are concerned with the conservation of historical heritage. Visitors are more concerned with dimensions intrinsically related to tourism. Originality/value - This research allowed to fill a gap found in the literature, namely, the importance of considering the perceptions of different actors in the urban landscape monitoring. These results are an important contribution for local authorities to understand the value of urban landscape elements from the perspective of residents and visitors. This study opened the possibility of comparing the results from different historical cities centres.